Study on the optimum pressure controllability of PID tuning by using different tuning rules - Zolkapali, Siti Norhana Fatehah (2017)
This study is carried out to determine the optimum pressure controllability by using various tuning rule hence identify the best tuning rule for pressure controllability. Delta V Emerson system is used on Gas Pressure Control Plant (PIC92). There are several analyses conducted in this study which are open loop analysis and closed loop analysis. The outcome of the open loop analysis is the process response of response rate (RR), dead time (Td) and time constant (Tc) and applied in various tuning rule. The method used for open loop test is Reformulated Tangent Method. Next, closed loop analysis is carried out by performing performance tests and fine tuning. This performance tests are conducted to observe and investigate the best and efficient tuning rule when the set point and load disturbance is changes. Then, the settling criteria of process response is determined for the settling time (Ts), percentage overshoot (%OV) and set point error (e). The controller that has minimum settling time and peak overshoot and less error will be considered as the best controller. Thus, in this study, the Cohen-Coon method is work well on a pressure controllability because it has minimum settling time and peak overshoot and also less set point error compared to the other tuning rule.